Evaluation of the resistance to Chinese predominant races of Puccinia triticina and analysis of effective leaf rust resistance genes in wheat accessions from the U.S. National Plant Germplasm System - Zhang, Lin; Zhao, Xuefang; Liu, Jingxian; Wang, Xiaolu; Gong, Wenping; Zhang, Quanguo; Liu, Yuping; Yan, Hongfei; Meng, Qingfang; Liu, Daqun (Frontiers in Plant Science, 2022)
Puccinia triticina, which is the causative agent of wheat leaf rust, is widely spread in China and most other wheat-planting countries around the globe. Cultivating resistant wheat cultivars is the most economical, effective, and environmentally friendly method for controlling leaf rust-caused yield damage. Exploring the source of resistance is very important in wheat resistance breeding programs. In order to explore more effective resistance sources for wheat leaf rust, the resistance of 112 wheat accessions introduced from the U.S. National Plant Germplasm System were identified using a mixture of pathogenic isolates of THTT, THTS, PHTT, THJT and THJS which are the most predominant races in China. As a result, all of these accessions showed high resistance at seedling stage, of which, ninety-nine accessions exhibited resistance at adult plant stage. Eleven molecular markers of eight effective leaf rust resistance genes in China were used to screen the 112 accessions. Seven effective leaf rust resistance genes Lr9, Lr19, Lr24, Lr28, Lr29, Lr38 and Lr45 were detected, except Lr47. Twenty-three accessions had only one of those seven effective leaf rust resistance gene. Eleven accessions carried Lr24+Lr38, and 7 accessions carried Lr9+Lr24+Lr38, Lr24+Lr38+Lr45, Lr24+Lr29+Lr38 and Lr19+Lr38+Lr45 respectively. The remaining seventy-one accessions had none of those eight effective leaf rust resistance genes. This study will provide theoretical guidance for rational utilization of these introduted wheat accessions directly or for breeding the resistant wheat cultivars.